2017
DOI: 10.1080/17482631.2017.1342504
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative phenomenological analysis of the subjective experience and understanding of the at risk mental state

Abstract: Over recent years there has been a growing interest in identifying the early stages of psychosis. The At Risk Mental State (ARMS) is characteristic of the prodromal stages of psychosis and its identification gives rise to a number of clinical and research opportunities including early intervention and prevention of psychosis. This study employs interpretative phenomenological analysis to gain insights into the subjective experience and individuals understanding of the development of their ARMS. Five participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
(66 reference statements)
2
7
0
Order By: Relevance
“…Although the majority of individuals did not define their self-concept in regard to their mental health, some participants discussed how mental health symptoms influenced their self-concept while other participants discussed how mental health experiences have changed them. These latter findings align with past research demonstrating the potential impact of mental health symptoms, stigma, and transitional events on one’s identity (Brew et al, 2017; Lally, 1989), and deserve further consideration in future research with individuals at CHR.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Although the majority of individuals did not define their self-concept in regard to their mental health, some participants discussed how mental health symptoms influenced their self-concept while other participants discussed how mental health experiences have changed them. These latter findings align with past research demonstrating the potential impact of mental health symptoms, stigma, and transitional events on one’s identity (Brew et al, 2017; Lally, 1989), and deserve further consideration in future research with individuals at CHR.…”
Section: Discussionsupporting
confidence: 86%
“…Given the emerging research in this area, no a priori hypotheses were made, and phenomenological procedures were used to develop themes. In our Conclusions section, we compare and contrast our findings to prior, formative phenomenological work with individuals at CHR (Ben-David et al, 2014;Brew et al, 2017). Data from similarly aged healthy controls (HCs) were also assessed for comparison.…”
Section: Present Studymentioning
confidence: 90%
See 1 more Smart Citation
“…Within the TSD, psychotic experiences had the unique characteristics of being frightening and/or perplexing, as well as catalysts for further distressing events such as hospitalization and/or legal difficulties. These findings mirror recent phenomenological studies of both attenuated or prodromal symptoms (Brew, Shannon, Storey, Boyd, & Mulholland, 2017; Hu, 2017) and FEP (Cabassa et al, 2018; Hansen, Stige, Davidson, Moltu, & Veseth, 2018), which have indicated that young adults struggle to understand anomalous experiences that initially seem unfamiliar.…”
Section: Discussionsupporting
confidence: 85%
“…Fowler et al , 2018; Ochoa et al , 2017), further attention has been paid to understanding the subjective experience of first episode psychosis (Boydell et al , 2010; Windell et al , 2015). Gaining an understanding of how adolescents make sense of their experiences of psychosis allows service providers to gain a deeper insight into how best to engage and support them (Brew et al , 2017). Researchers investigating the prodromal period using in-depth interviews with adolescents have identified a wide range of symptoms and behaviours including sleep difficulties, anxiety, problems with concentration, racing thoughts and social withdrawal (Corcoran et al , 2003; MacBeth et al , 2014; McCarthy-Jones et al , 2012).…”
Section: Introductionmentioning
confidence: 99%